Hybrid Breeding for Restoration of Threatened Forest Trees: Evidence for Incorporating Disease Tolerance in Juglans cinerea - Brennan, Andrea N.; McKenna, James R.; Hoban, Sean M.; Jacobs, Douglass F. (Frontiers in Plant Science, 2020)
Hybridization is a potential tool for incorporating stress tolerance in plants, particularly to pests and diseases, in support of restoration and conservation efforts. Butternut (Juglans cinerea) is a species for which hybridization has only recently begun being explored. This North American hardwood tree is threatened due to Ophiognomonia clavigignenti-juglandacearum (Ocj), the causal fungus of butternut canker disease (BCD), first observed in 1967. Observational evidence in some wild J. cinerea populations indicates that naturalized hybrids of J. cinerea with Japanese walnut (Juglans ailantifolia) may be more tolerant to BCD than non-admixed J. cinerea, but this has not been formally tested in a controlled trial. We aimed to examine potential BCD tolerance within and between J. cinerea and J. cinerea × J. ailantifolia hybrids and to determine if there is a difference in canker growth between BCD fungal isolates. Five-year-old J. cinerea and hybrid trees were inoculated with two Ocj fungal isolates collected from natural infections found in two different sites in Indiana, United States, and a blank control (agar only). Measurements of both artificially induced and naturally occurring cankers were taken at 8-, 12-, 20-, 24-, and 32-month post-inoculation. Differences in canker presence/absence and size were observed by fungal isolate, which could help explain some of the differences in BCD severity seen between J. cinerea populations. Smaller and fewer cankers and greater genetic gains were seen in hybrid families, demonstrating that hybrids warrant further evaluation as a possible breeding tool for developing BCD-resistant J. cinerea trees.